(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2022)
Technological solutions for the construction of sludge barns at the Pereschepynskoye deposit are considered and analyzed. The authors proposed to arrange a monolithic vertical anti-filtration curtain of the type "wall in the soil" of soil-cement elements. When filling the sludge storage, it is proposed to fill with waste using the following technology: pour a layer of waste about 1 m thick on the bottom of the sludge storage, then pour a layer of soil on top of the construction site (humidity 4-5%) up to 1 m. drying it is offered to add ash of removal of the Mykolaiv thermal power plant. The amount of additive is from 1.5 to 3% depending on the type of soil. The thickness of the layers is selected and calculated to obtain the optimum moisture content of the sludge and soil mixture